EXPERIENCE OF GROWING PIKEPERCH IN THE CONDITIONS OF THE SRC "FISHERIES" (Experimental biology, 2021)
Scientific research was carried out in the scientific research center "Fisheries" of the NCJSC "Kazakh Agrotechnical University S. Seifullin" on the artificial cultivation of pikeperch  in recirculating aquatic system (RAS) in accordance with the grant program of the Ministry of Education and Science of the Republic of Kazakhstan.The purpose of our research is to work out the technological processes of keeping commercial pikeperch in the conditions of RAS.To achieve this goal, the following tasks were defined:- Study of the temperature and hydrochemical regime in the ultrasonic system during the cultivation of pikeperch;- To study the morphobiological parameters of pikeperch when growing in RAS.The biotechnical methods of growing pikeperch in closed water supply installations were worked out, the hydrochemical regime was monitored, and the growth and development of pikeperch was carried out when kept in the basins of RAS.
Keywords: recirculating aquatic system, fish tanks, pikeperch, hydrochemical mode